Effect of Industrial Effluents on the Germination and Seedling Growth of Three Leafy Vegetables - Begum, Shameem Ara; Alam, M Jahangir; Rahman, Syed Shayfur; Rahman, M Mizanur (Bangladesh Journal of Scientific and Industrial Research, 2010)
This study was conducted to determine the effect of industrial effluents on seed germination and seedling growth of some leafy vegetables under pot culture condition. Waste water sample was collected from natural gas fertilizer factory Limited, Fenchuganj, Sylhet. Four different leafy vegetables were selected as test crop to grow using these effluents. The design of the experiment was randomized complete block. The effects of different concentration of effluent were compared to that of distilled water (control). The results revealed that different concentrations of the extract caused significant inhibitory effect on germination and root elongation but benefited the shoot elongation. Maximum reduction in germination and root length was observed with the increase in effluent concentration, but increasing the shoot length. Bioassays indicated that the effects were proportional to the concentrations of the effluents and higher concentration showed stronger effect. Different physicochemical parameters of water e.g. pH, temperature, conductivity, dissolved oxygen (DO), chemical oxygen demand (COD), turbidity, Total dissolve solids (TSS), total suspended solids (TSS) etc. of the sample was also analyzed. It was found that the values were far apart from the optimum values that require for safe aquatic environment to establish an aquatic ecosystem on water body. It can be concluded that polluted water is becoming a threat for the crops and also for aquatic environment with the passage of time as more and more wastes are becoming a part of it. Key words: Industrial effluents; Aquatic environment; Seed germination; Seedling growth; Pollution. DOI: 10.3329/bjsir.v45i2.5705 Bangladesh J. Sci. Ind. Res. 45(2), 101-104, 2010